Business Ethics in a Global Economy: A Cross-Cultural Study Among Working Adults in Russia and Vietnam. Issue 4 (August 2019) - Nguyen, Lam D.; Pham, Loan N. T.; Ermasova, Natalia
Abstract: The purpose of the present study is to empirically examine the personal perception of working adults on business ethics in Russia and Vietnam. Data were collected with the help of a questionnaire from 487 working adults (248 Russian and 239 Vietnamese adults). Significance of differences in Clark and Clark's Personal Business Ethics Scores based on gender, management experience and ethics training was analysed with the help of univariate analysis of variance method (two-way analysis of variance method). Findings of the present study indicate that there is a significant difference in the level of ethical maturity among the Vietnamese and Russian working adults. Vietnamese respondents have higher business ethics perception than Russian respondents. Female adults demonstrate higher ethical maturity level than their male counterparts in the overall sample. Additionally, there is no significant difference in the business ethics perception of respondents in Russia and Vietnam on the basis of ethics training and management experience. This study provides global business leaders an opportunity to better understand business ethics perception of working adults across Russia and Vietnam.